IMPLEMENTASI UNDANG-UNDANG TINDAK PIDANA PENCUCIAN UANG (TPPU) DI INDONESIA (SUATU GAMBARAN TENTANG PENGETAHUAN DAN APLIKASI APARAT PENYIDIK PENUNTUT UMUM DAN PPATK) - Sabatini Sabatini (Jurnal Kriminologi Indonesia, 2010)
Discrepancy of general knowledge having law enforcement agents on the law model in the criminal justice system in Indonesia, makes the due process of law enforcement officials in applying the Law on Money Laundering (AML) far from optimal. The reviewed knowledge of the law enforcement agents covers investigation process, making indictment, as well as coordination among judiciary institutions, namely the Police as investigators, the Attorney General as prosecutors, and independent institutions for INTRAC (PPATK) as parties involved in providing Consolidated Results Analysis (LHA) of the AML. Due process model with its inhibiting factors ensures the presumption of innocence, thus very carefully promotes the formal process in accordance with the Criminal Procedure Code. As a result, the process has become cumbersome bureaucracy, and slow in dealing with cases of AML. The statistical test conducted using frequency and crosstab shows that due process model emphasizes the Criminal Procedure Code, particularly in terms of implementing investigation and prosecution function. This apparently has created disharmony among officials who perform their respective functions. This disharmony ultimately leads to charges of improper gift in capturing the perpetrators of AML. Attorney General as a party that makes the charges against perpetrators of AML cannot function maximally because it does not interfere the investigation process conducted by the police.Eventually, their knowledge levels of and capabilities to apply AML cases are less than optimal. This problem eventually leads to only 27 cases that utilizing AML Law within period of five years. This study finds that there is a need for law enforcement agents to harmonize the investigation utilizing the Attorney General description of general knowledge and application of AML Law.